Stress Level Among Caregivers of Thalassemia Patients - Inamdar, Shivansh; Inamdar, Madhuri; Gangrade, Anila (National Journal of Community Medicine, 2015)
Introduction: Children with Thalassemia have to regularly attend hospital for blood transfusion and chelation therapy. Parents suffer from psychosocial burden because of expenses, stress and fear of death. Material and Methods: It is a cross sectional interview based study. Thirty five Care giving parents were interviewed in the day care cen- tre of anemia in Choithram Hospital Indore. Two proformas were used. One for general information and the other one was the Zarit Burden Interview scale. Results: The parents were under stress (60.6%).There was no differ- ence statistically between school and college educated caregivers of psychosocial burden. Knowledge regarding prevention of Thalasse- mia by pre marriage genetic counseling and testing was very poor among parents. Conclusion: The parents of Thalassemic children need to receive health education about the disease and required treatment. They need psychosocial counseling and support.